Effect of occupational co-exposure to lead and cadmium on selected immunomodulatory cytokines. (January 2022) - Goyal, Taru; Mitra, Prasenjit; Singh, Preeti; Sharma, Shailja; Purohit, Purvi; Sharma, Praveen
Occupational exposure to heavy metals like lead (Pb) and cadmium (Cd) is associated with the development of several diseases. The objective of this study was to determine the effect of occupational co-exposure to Pb and Cd on the blood levels of selected immune-modulatory cytokines related to T helper (Th), that is, Th1, interleukin-2 (IL-2), Th2, (IL-4 and IL-10), and Th17, (IL-17) cells. The study comprised 207 individuals divided into two groups: exposed ( n = 110) and nonexposed ( n = 97). Blood Pb and Cd were determined using Graphite Furnace Atomic Absorption Spectroscopy, and serum levels of cytokines were measured using enzyme-linked immunosorbent assay (ELISA). The study revealed significantly higher blood Pb and Cd levels in the exposed group. A significant decrease in Th1 cytokine-IL-2 and Th2 cytokine-IL-10 was found, while IL-4 (Th2 cytokine) and IL-17 (Th17) levels were higher in the exposed group. In the mixed exposure analysis, among all the selected cytokines, IL-4 levels were significantly different between individuals having higher levels of both Pb and Cd versus lower levels of Pb and Cd. While IL-2 levels were highest among the low Pb and Cd group, the IL-17 levels were highest among individuals with higher Cd levels. The study demonstrated that co-exposure to low levels of Pb and Cd might have an immune-modulatory effect. The data suggested a metal-induced pro-inflammatory immune response.